Distal Femur Allograft Prosthetic Composite Reconstruction for Short Proximal Femur Segments following Tumor Resection - Bryan S. Moon; Nathan F. Gilbert; Christopher P. Cannon; Patrick P. Lin; Valerae O. Lewis (Advances in Orthopedics)
Short metaphyseal segments remaining after distal femoral tumor resection pose a unique challenge. Limb sparing options include a short stemmed modular prosthesis, total endoprosthetic replacement, cross-pin fixation to a custom implant, and allograft prosthetic composite reconstruction (APC). A series of patients with APC reconstruction were evaluated to determine functional and radiologic outcome and complication rates. Twelve patients were retrospectively identified who had a distal femoral APC reconstruction between 1994 and 2007 to salvage an extremity with a segment of remaining bone that was less than 20 centimeters in length. Seventeen APC reconstructions were performed in twelve patients. Eight were primary procedures and nine were revision procedures. Average f/u was 89 months. Twelve APC reconstructions (71%) united and five (29%) were persistent nonunions. At most recent followup 10 patients (83%) had a healed APC which allowed WBAT. One pt (8%) had an amputation and one pt (8%) died prior to union. Average time to union was 19 months. Four pts (33%) or five APC reconstructions (29%) required further surgery to obtain a united reconstruction. Although Distal Femoral APC reconstruction has a high complication rate, a stable reconstruction was obtained in 83% of patients.